2021
DOI: 10.1007/s11845-021-02698-w
|View full text |Cite
|
Sign up to set email alerts
|

Professional and personal opinions of doctors in training during the first wave of the COVID19 pandemic

Abstract: Background The COVID19 pandemic is one of the greatest modern global healthcare crises. The resultant morbidity and mortality of public and healthcare professionals has led to psychological impacts and economic repercussions. We set out to assess the concerns of doctors in training during this crisis. Methods A questionnaire was developed and delivered via Survey Monkey to doctors in training from 27 March to 6 April 2020, 2 weeks prior to the expected surge in Ireland … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
4
1
Order By: Relevance
“…These findings resemble similar Australian research showing that junior doctors, healthcare workers, and the general population expressed higher levels of concern about others contracting COVID-19 than about contracting COVID-19 themselves. [30][31][32]40 In the present sample, caring for patients who contracted COVID-19 did not predict COVID-19-related anxieties or symptoms of common mood disorders, although one-third of junior doctors who took part in the present study were aware that they were potentially exposed to the virus at their workplace. There is conflicting evidence as to whether junior doctors who were exposed to the novel virus experienced elevated symptoms of poor mental health.…”
Section: Exploration Of Covid-19-related Anxietycontrasting
confidence: 63%
“…These findings resemble similar Australian research showing that junior doctors, healthcare workers, and the general population expressed higher levels of concern about others contracting COVID-19 than about contracting COVID-19 themselves. [30][31][32]40 In the present sample, caring for patients who contracted COVID-19 did not predict COVID-19-related anxieties or symptoms of common mood disorders, although one-third of junior doctors who took part in the present study were aware that they were potentially exposed to the virus at their workplace. There is conflicting evidence as to whether junior doctors who were exposed to the novel virus experienced elevated symptoms of poor mental health.…”
Section: Exploration Of Covid-19-related Anxietycontrasting
confidence: 63%
“…For example, as outlined in the Results section under the ‘Challenges to health and well-being’ theme, we note that Brazilian interviewees highlighted the impact of PPE shortages during the early stage of the pandemic crisis, whereas PPE availability was not cited as an issue by our Irish interviewees. This is because PPE availability for Irish healthcare staff was perceived to be sufficient at the time of data collection (October 2020) compared with earlier in the pandemic (March to April 2020) 59. The cross-sectional design of the study precluded a more nuanced examination of the challenges faced by junior doctors which would likely fluctuate across the phases of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…This is because PPE availability for Irish healthcare staff was perceived to be sufficient at the time of data collection (October 2020) compared with earlier in the pandemic (March to April 2020). 59 The cross-sectional design of the study precluded a more nuanced examination of the challenges faced by junior doctors which would likely fluctuate across the phases of the COVID-19 pandemic.…”
Section: Open Accessmentioning
confidence: 99%
“…This study indicated that working position was significantly associated with preparedness and work impact, higher number of working years was significantly associated with higher work impact, and work overload was significantly related to work impact, personal life impact, and concerns. A previous study showed that almost 80 % of healthcare workers felt somewhat or well prepared to treat patients with COVID-19 ( Farooq et al, 2022 ). In this study, nurses showed the highest levels of preparedness.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare workers have the duty to care for both patients with and without COVID-19 while also protecting themselves and their own families from infection. An Irish survey on stress among doctors during COVID-19 found that the majority of respondents had moderate stress prior to any COVID-19 surge ( Farooq et al, 2022 ). It was reported that concerns regarding their family and the risk of infecting their family members were major factors that undermined the performance of healthcare workers during the pandemic ( Rafi et al, 2021 , Hossain and Clatty, 2021 ), with family health (86 %), personal health (72 %), and social life (17 %) being their primary concerns.…”
Section: Discussionmentioning
confidence: 99%